Kombinasi Tanaman Penghalang, Kitosan, dan Ekstrak Daun Bugenvil untuk Pengelolaan Virus pada Tanaman Kedelai - Cahyati, Iwe; Damayanti, Tri Asmira; Santoso, Sugeng (Jurnal Fitopatologi Indonesia, 2023)
Combination of Barrier Crop, Chitosan, Bougaivillea Leaf Extract to Manage Virus on Soybean Viral infection is one of the limiting factor of soybean production in Indonesia. This study aimed to test the effectiveness of chitosan, bougainvillea leaf extract, and their combinations as well as insecticide as comparison treatment in controlling virus infections on soybeans in the field. The effectiveness of treatments were tested in main plot with and without maize as barrier plants. Disease assessment, insect population, and agronomic variables were observed weekly. The aphid population in the control treatment with barrier plants showed significantly lower than control without barrier plants, indicating that barrier plants able to hindered aphids to enter the soybean crops. Incorporating of chitosan, bougainvillea leaf extract, and their combination treatments able to control aphid population comparable to insecticide treatment in both main plots. The low AUPPC of aphid populations were in line with lower disease incidence, severity in compared to AUDPC of control treatments. The effectiveness of treatments in plot with barrier plants able to reduced aphid population and disease intensity higher than similar treatments in main plot without barrier plants. The AUDPC among chitosan, bougainvillea leaf extract, combination, and insecticide treatments was significantly lower in both main plots in compared to control treatment. Soybean yields showed significantly higher in chitosan, bougainvillea leaf extract, and combination treatment than control treatments in both main plots. The utilization of maize as barrier plants incorporated by one of chitosan and/or bougainvillea leaf extract will become a eco-friendly management package to control viruses infecting soybean in the field.